Current evidence and practical applications of flywheel eccentric overload exercises as postactivation potentiation protocols: A brief review - Beato, M.; McErlain-Naylor, S. A.; Halperin, I.; Dello Lacono, A. (International Journal of Sports Physiology and Performance, 2020)
This review summarizes the current evidence regarding postactivation potentiation (PAP) strategies using flywheel eccentric overload (EOL) exercises. The first section covers the PAP phenomenon, its underpinning neurophysiological mechanisms, and commonly used PAP protocols. The second section describes the characteristics of flywheel ergometers and the rationale for using EOL to induce PAP effects. The third section summarizes the growing literature, which has evaluated the onset, time course, and magnitude of PAP effects on athletic performance using EOL exercises. Finally, this review reports some practical recommendations on how PAP effects can be elicited using EOL exercises in applied settings and proposes future research directions.